2013
DOI: 10.1111/ijac.12081
|View full text |Cite
|
Sign up to set email alerts
|

Flexible Hydrophobic and Lipophilic Aluminum‐Doped Silicon Carbide Fibrous Mats Synthesized by Electrospinning Polyaluminocarbosilane

Abstract: Flexible aluminum-doped silicon carbide (SiC(Al)) fibrous mats were synthesized by combining electrospinning and polymer-derived ceramic techniques. The mats consist of three-dimensional network structure with randomly distributed fibers of approximately 1.5 lm diameter. The obtained mats exhibited simultaneous fairly good hydrophobic and lipophilic behavior without the need of any posttreatment. Given the intrinsic oxidation/corrosion resistance of Al-doped SiC, the ceramic mats obtained here could be very pr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
5
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(5 citation statements)
references
References 27 publications
0
5
0
Order By: Relevance
“…Therefore, there is a need to explore the growth of 1D 3C-SiC nanostructures by using other metal catalysts in the form of thin films and particles, so that, better understanding about the catalytic growth mechanism, growth morphology, and growth density of 1D 3C-SiC nanostructures is needed which can be helpful for a particular application, such as fabrication of stable superhydrophobic surfaces. Though SiC is an intrinsically hydrophilic material, however, one of the important applications of the SiC 1D nanostructures could be in the fabrication of superhydrophobic surfaces as some researchers have already demonstrated the superhydrophobic behavior of SiC after modification with low surface energy materials. Moreover, there are only few reports available related to the superhydrophobic behavior of SiC 1D nanostructures after modification with low surface energy coatings, such as tubular cubic SiC nanostructured film, aligned SiC NW crossed nets, aluminum-doped SiC fibrous mats, SiC–SiO 2 core–shell NWs, and carbon-sheathed SiC nanocables . In the above-mentioned studies, the growth morphology and time- and temperature-dependent wetting behavior of SiC 1D nanostructures using different metal catalysts have not been studied; therefore, there is also a need to carry out these kinds of studies.…”
Section: Introductionmentioning
confidence: 99%
“…Therefore, there is a need to explore the growth of 1D 3C-SiC nanostructures by using other metal catalysts in the form of thin films and particles, so that, better understanding about the catalytic growth mechanism, growth morphology, and growth density of 1D 3C-SiC nanostructures is needed which can be helpful for a particular application, such as fabrication of stable superhydrophobic surfaces. Though SiC is an intrinsically hydrophilic material, however, one of the important applications of the SiC 1D nanostructures could be in the fabrication of superhydrophobic surfaces as some researchers have already demonstrated the superhydrophobic behavior of SiC after modification with low surface energy materials. Moreover, there are only few reports available related to the superhydrophobic behavior of SiC 1D nanostructures after modification with low surface energy coatings, such as tubular cubic SiC nanostructured film, aligned SiC NW crossed nets, aluminum-doped SiC fibrous mats, SiC–SiO 2 core–shell NWs, and carbon-sheathed SiC nanocables . In the above-mentioned studies, the growth morphology and time- and temperature-dependent wetting behavior of SiC 1D nanostructures using different metal catalysts have not been studied; therefore, there is also a need to carry out these kinds of studies.…”
Section: Introductionmentioning
confidence: 99%
“…One of the promising applications of 3C-SiC is in the fabrication of superhydrophobic surfaces. Basically SiC is a hydrophilic material [30][31][32], but when modified with some specific low surface energy materials, it exhibits superhydrophobic behavior [32][33][34][35]. Kwak et al [36] reported the superhydrophobic behavior of SiC-SiO 2 core-shell nanowires modified by dip-coating alkyltrichlorosilane.…”
Section: Introductionmentioning
confidence: 99%
“…Hence, they can slide against each other to lower stress concentration during bending. 30 The exibility of the mat facilitates its practical use in sophisticated devices.…”
Section: Resultsmentioning
confidence: 99%
“…[22][23][24][25][26] However, investigations based on the combination of electrospinning and PDCs, not to mention ceramic bers with a radial gradient composition, are limited. [27][28][29][30] In our present work, we illustrate the fabrication of novel ZrO 2 /SiC bers with a gradient composition via electrospinning of the precursor containing zirconium n-butoxide (Zr(OC 4 H 9 ) 4 ) as a low-molecular-mass additive and PCS as a SiC precursor, followed by maturation and subsequent pyrolysis. During maturation, the as-prepared bers exhibited a gradient structure from the surface towards the center.…”
Section: Introductionmentioning
confidence: 99%